NCREASING THE LEVEL OF DIESEL FUEL COMBUSTION DUE TO IMPROVING ITS QUALITY (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
This article describes the combustion process of diesel fuel in terms of two main parameters - cetane number (determining engine power and economic indicators) and fractional composition (determining the completeness of fuel combustion, engine smoke and exhaust toxicity).
Keywords: Fraction, cetane number, flash point, stability, combustion chamber, environmen- tal friendliness.